Parasitic Architecture and the Conversion of Abandoned Buildings into Green Open Space - Pratama, Pandhu Putra; Hayati, Arina; Dinapradipta, Asri (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 10 No 1 (2023): April 2023, 2023)
In several big cities in Indonesia, there are numerous cases of abandoned buildings due to delays in the construction process. Some of these buildings even remain abandoned and underused for an extended period. In line with this condition, cities experience a high level of urbanization that cause places tremendous pressure on urban spaces, especially green open spaces. This paper discusses Parasitic Architecture as an alternative design approach to address this issue. It proposes to use abandoned buildings as public facilities and is presented in sections. First, it reviews the concepts and principles of Parasitic Architecture, followed by observational studies using a contextual analysis to explore the context and function of abandoned buildings. The exploration results indicate a potential to apply Parasitic Architecture's concepts and principles in redesigning abandoned buildings and turning them into public facilities, particularly into green open spaces. In this context, the paper views Parasitic Architecture plays a vital role in providing innovative spatial and structural configurations to reorient the use of unused buildings for public functions. Keywords: abandoned building; contextual analysis; parasitic architecture; green open space Abstrak Di beberapa kota besar di Indonesia, banyak kasus bangunan terbengkalai akibat adanya kemunduran dalam proses konstruksi. Beberapa dari bangunan tersebut malahan terlalaikan dan tidak dimanfaatkan dalam jangka waktu yang lama. Seiring dengan permasalahan ini, kota-kota besar mengalami peningkatan jumlah urbanisasi yang menyebabkan ruang perkotaan semakin berkurang termasuk untuk ruang terbuka hijau kota. Paper ini membahas bagaimana parasitic architecture digunakan sebagai pendekatan perancangan untuk merespon permasalahan dengan memanfaatkan bangunan terbengkalai agar dapat berfungsi kembali dan dijadikan sebagai fasilitas atau ruang publik. Pertama, dilakukan kajian teori tentang konsep dan prinsip parasitic architecture , dilanjutkan dengan mengeksplorasi konteks dan fungsi bangunan terbengkalai melalui studi observasi dengan analisis kontekstual. Hasil eksplorasi menjelaskan terdapat potensi untuk menerapkan konsep dan prinsip parasitic architecture dalam perancangan kembali bangunan terbengkalai menjadi fasilitas publik, khususnya ruang terbuka hijau. Dalam konteks ini, parasitic architecture dipandang sebagai pendekatan perancangan berperan penting dalam pengadaan konfigurasi ruang dan struktur inovatif yang mampu mengalihkan bangunan terbengkalai menjadi ruang berfungsi publik.  Kata kunci: bangunan terbengkalai; analisis kontesktual; parasitic architecture ; ruang terbuka hijau